(untitled) (Swiss Medical Weekly, 2026)
AIMS OF THE STUDY: On 1 September 2011, donation after circulatory death (DCD) organ donation resumed in Switzerland after the DCD programme had been suspended for four years due to jurisdictional and medico-ethical discrepancies. DCD has gained relevance due to the worldwide scarcity of donor organs and now accounts for nearly half of all donations in the Swiss transplant setting. This study aimed to identify risk and protective factors for the occurrence of delayed graft function, which is a common early complication following kidney transplantation, especially in DCD transplants. METHODS: This retrospective cohort study included all Swiss DCD kidney transplants performed between 1 September 2011 and 31 August 2024. The primary outcome was the occurrence of delayed graft function, defined as the need for dialysis within the first week following kidney transplantation. A complete-data, multivariable analysis using a logistic regression model for the event of delayed graft function was conducted for the following variables: donor age and donor comorbidity, cause of death, year of transplantation, functional warm and cold ischaemia time, use of abdominal normothermic regional perfusion, and use of hypothermic machine perfusion. RESULTS: Of 499 controlled DCD donors, 351 were kidney donors. These donors enabled a total of 711 kidney transplants, including 7 double kidney transplants. Of the 650 recipients who qualified for analysis, 315 (48.5%) experienced delayed graft function. Odds ratios for delayed graft function were 0.18 (0.09–0.33) for procurement with abdominal normothermic regional perfusion, 0.55 (0.36–0.83) for preservation with hypothermic machine perfusion, 1.00 (0.73–1.36) for functional warm ischaemia time, and 1.33 (1.01–1.73) for cold ischaemia time. CONCLUSIONS: A statistically significant decrease in delayed graft function risk was observed for the use of abdominal normothermic regional perfusion and hypothermic machine perfusion. No evidence was found for an association between functional warm ischaemia time and delayed graft function, and only weak evidence was found for cold ischaemia time. These findings underscore the effectiveness of modern procurement and preservation methods used in kidney transplantation and are consistent with current research findings.